Interplay of cytokines in the pathophysiology of atopic dermatitis: insights from Murin models and human - Yamamura, Yuto; Nakashima, Chisa; Otsuka, Atsushi (Frontiers in Medicine, 2024)
The pathogenesis of atopic dermatitis (AD) is understood to be crucially influenced by three main factors: dysregulation of the immune response, barrier dysfunction, and pruritus. In the lesional skin of AD, various innate immune cells, including Th2 cells, type 2 innate lymphoid cells (ILC2s), and basophils, produce Th2 cytokines (interleukin (IL)-4, IL-5, IL-13, IL-31). Alarmins such as TSLP, IL-25, and IL-33 are also produced by epidermal keratinocytes, amplifying type 2 inflammation. In the chronic phase, not only Th2 cells but also Th22 and Th17 cells increase in number, leading to suppression of filaggrin expression by IL-4, IL-13, and IL-22, which further deteriorates the epidermal barrier function.Dupilumab, which targets IL-4 and IL-13, has shown efficacy in treating moderate to severe AD. Nemolizumab, targeting IL-31RA, effectively reduces pruritus in AD patients.In addition, clinical trials with fezakinumab, targeting IL-22, have demonstrated promising results, particularly in severe AD cases. Conversely, in murine models of AD, several cytokines, initially regarded as promising therapeutic targets, have not demonstrated sufficient efficacy in clinical trials. IL-33 has been identified as a potent activator of immune cells, exacerbating AD in murine models and correlating with disease severity in human patients. However, treatments targeting IL-33 have not shown sufficient efficacy in clinical trials. Similarly, thymic stromal lymphopoietin (TSLP), integral to type 2 immune responses, induces dermatitis in animal models and is elevated in human AD, yet clinical treatments like tezepelumab exhibit limited efficacy. Therapies targeting IL-1α, IL-5, and IL-17 also failed to achieve sufficient efficacy in clinical trials.It has become clear that for treating AD, IL-4, IL-13, and IL-31 are relevant therapeutic targets during the acute phase, while IL-22 emerges as a target in more severe cases. This delineation underscores the necessity of considering distinct pathophysiological aspects and therapeutic targets in AD between mouse models and humans. Consequently, this review delineates the distinct roles of cytokines in the pathogenesis of AD, juxtaposing their significance in human AD from clinical trials against insights gleaned from AD mouse models. This approach will improve our understanding of interspecies variation and facilitate a deeper insight into the pathogenesis of AD in humans.